PCR Fingerprinting of Candida albicans Associated with Chronic Hyperplastic Candidosis and Other Oral Conditions - Bartie, Kerry L. (American Society for Microbiology, 2001)
The purpose of this study was to genotype strains of Candida albicans to determine whether specific types were associated with chronic hyperplastic candidosis (CHC). A total of 67 candidal isolates from CHC patients (n = 17) and from patients with other oral conditions (n = 21) were genotyped by PCR fingerprinting employing two interrepeat primer combinations (1245 and 1246 primers or 1251 primer) and a single minisatellite-specific M13 primer. The most suitable primer for fingerprint analysis was found to be primer 1251, yielding well-resolved banding patterns. For the 67 isolates tested, PCR fingerprinting delineated 25 (1245 and 1246 primers), 27 (1251 primer), and 25 (M13 primer) profiles. The majority of C. albicans isolates from multiple sites within the mouth produced identical profiles (six out of nine subjects examined). For patients for whom a series of longitudinal isolates was available, strain persistence for up to 7 years was evident for five out of eight individuals, despite episodes of antifungal therapy. Computer-assisted comparison of the interrepeat PCR fingerprints identified seven distinct profiles that were shared among isolates from different individuals. However, no association was evident among isolates of C. albicans from specific clinical conditions. Eight isolates that were initially identified as C. albicans but having atypical PCR profiles were later confirmed as Candida dubliniensis. In conclusion, the genotypic data do not indicate clonal restriction of C. albicans with respect to CHC. Furthermore, these results have demonstrated that in the majority of individuals, colonizing populations of C. albicans are clonal in nature and exhibit strain persistence.